Environmental incidents and sustainability pricing provisions - Huyen Nguyen; Sochima Uzonwanne (Halle Institute for Economic Research (IWH), 2024)
We investigate whether lenders employ sustainability pricing provisions to manage borrowers' environmental risk. Using unexpected negative environmental incidents of borrowers as exogenous shocks that reveal information on environmental risk, we find that lenders manage borrowers' environmental risk by conventional tools such as imposing higher interest rates, utilizing financial and net worth covenants, showing reluctance to refinance, and demanding increased collateral. In contrast, the inclusion of sustainability pricing provisions in loan agreements for high environmental risk borrowers is reduced by 11 percentage points. Our study suggests that sustainability pricing provisions may not primarily serve as risk management tools but rather as instruments to attract demand from institutional investors and facilitate secondary market transactions.
Keywords: G21; G28; K21; 330; bank monitoring; environmental risk; institutional investors; sustainability pricing provisions